The association between cardiovascular risk and physical performance in individuals with obesity: A cross-sectional study focusing on the 5× sit-to-stand test - de Paula Chaves Freitas, Jaqueline; da Costa Teixeira, Leonardo Augusto; Santos, Joyce Noelly Vitor; de Moraes, Daniela Barreto; da Silva Lage, Vanessa Kelly; Gonçalves, Gabriele Teixeira; Figueiró, Maria Thereza Otoni; Cunha, Tamara; Danielewicz, Ana Lúcia; Figueiredo, Pedro Henrique Sheidt; Sartorio, Alessandro; Taiar, Redha; et al. (International Journal of Cardiology, 2025)
Introduction Although it is established that individuals with obesity are at increased risk of cardiovascular events, the relationship between cardiovascular risk and physical function in this population is still a topic of discussion. The objectives of the present study were: to check the association between cardiovascular risk and physical performance through physical-functional tests and to identify cutoff points for functional tests to be used for the definition of high cardiovascular risk. Methods A cross-sectional study included adults, both sexes, with obesity. Dual X-ray absorptiometry was used to assess body composition, Jamar® dynamometer to assess handgrip strength, and the sit-to-stand test to a chair with 5 repetitions and 60 s for physical performance analysis. The Framingham global risk score was used to determine cardiovascular risk. Results The sample consisted of 192 individuals with obesity, aged between 20 and 74 years (mean ± SD: 42.6 ± 12.7 years). The group with high cardiovascular risk presented worse values of handgrip strength and physical performance (p < 0.05). After adjusting for age, the 5× sit-to-stand test was associated (β = 0.21; OR = 1.24 [95 %CI = 1.05-1.45]; p = 0.007) with high cardiovascular risk, and the cutoff point of 16 s for performing the test was found to be discriminatory of high cardiovascular risk in obesity. Conclusion The findings indicate that clinical assessment tools, specifically those that assess the functionality of individuals with obesity, are related to an increased risk of cardiovascular events. The 5× sit-to-stand test showed good diagnostic accuracy in this context.
Keywords: Cardiovascular risk; Handgrip strength; Obesity; Physical performance; Sit-to-stand test